2021
DOI: 10.1002/ajh.26271
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular phenotypes predict clinical outcomes in sickle cell disease: An echocardiography‐based cluster analysis

Abstract: This study sought to link cardiac phenotypes in homozygous Sickle Cell Disease (SCD) patients with clinical profiles and outcomes using cluster analysis. We analyzed data of 379 patients included in the French Etendard Cohort. A cluster analyses was performed based on echocardiographic variables, and the association between clusters, clinical profiles and outcomes was assessed. Three clusters were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
0
5
1
Order By: Relevance
“…Our data extend previous reports on an independent association between E/e′ at rest and % VO 2peakth or 6-min walk distance in SCA patients, suggestive of existing atrial cardiomyopathy 13,18,20 . However, we did not find such discriminant abnormalities on resting echocardiography, highlighting the challenge of diagnosing diastolic dysfunction in resting conditions in SCA population 15,16 . Thus, our results suggest that diastolic stress test during sub-maximal exercise is a valuable and safe tool in the early detection of subtle cardiac impairment in SCA patients.…”
Section: Stress-induced Diastolic Dysfunction Is Associated With Poor...contrasting
confidence: 78%
See 1 more Smart Citation
“…Our data extend previous reports on an independent association between E/e′ at rest and % VO 2peakth or 6-min walk distance in SCA patients, suggestive of existing atrial cardiomyopathy 13,18,20 . However, we did not find such discriminant abnormalities on resting echocardiography, highlighting the challenge of diagnosing diastolic dysfunction in resting conditions in SCA population 15,16 . Thus, our results suggest that diastolic stress test during sub-maximal exercise is a valuable and safe tool in the early detection of subtle cardiac impairment in SCA patients.…”
Section: Stress-induced Diastolic Dysfunction Is Associated With Poor...contrasting
confidence: 78%
“…Indeed, cardiovascular abnormalities at rest, such as pulmonary hypertension (PH) and diastolic dysfunction, have been identified as the leading cause of mortality and impaired quality of life in SCA patients [10][11][12][13][14] . These disorders rely on complex mechanisms associating chronic anemia, hemolysis-induced vasculopathy and repeated vaso-occlusive episodes, contributing to a maladaptive cardiovascular remodeling [15][16][17] . While the diagnosis of cardiac dysfunction is extremely challenging considering the unique hemodynamic features of SCA, recent studies have reported the potential interest of investigating cardiovascular adaptation during exercise, to dynamically unmask latent heart dysfunction and its association with exercise limitation [18][19][20] .…”
mentioning
confidence: 99%
“…Currently, data-driven unsupervised clustering is more widely used in the medical field, for example, in electronic medical records [44,45], medical decision making [46,47], and medical image analysis [8,9,48]. Additionally, several digital pathology studies have adopted unsupervised clustering to represent various features [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Supervised learning as a mainstay has been leveraged to improve disease diagnosis and has achieved substantial advancements by taking advantage of hand-crafted pathomics features [4], end-to-end deep learning [5,6], or a combination of such approaches [7]. Unsupervised learning is increasingly employed as a knowledge discovery approach to find meaningful intrinsic patterns in data, complementing supervised learning and enhancing biomedical image diagnostic performance [8,9]. However, few studies have explored the potential role of machine learning algorithms in evaluating lymphomas [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to keep in mind that the present results have been obtained in patients without systemic complications, at steady state (see supplemental) and particularly without cardiovascular impairment. Indeed, cardiovascular complications are one of the leading causes of functional impairment and mortality in SCD [52][53][54] . Therefore, our results cannot be extended to more severe populations, requiring dedicated trials currently underway.…”
Section: Experimental Considerations and Future Directionsmentioning
confidence: 99%